A rare case of bacteremia due to Acinetobacter junii in an immunocompetent adult - Nazir, Asifa; Farooq, Rumana; Nahvi, Nahid (International Journal of Research in Medical Sciences, 2016)
The genus Acinetobacter comprises a complex and heterogeneous group of bacteria, many of which are capable of causing a range of opportunistic, often nosocomial, infections in humans. Acinetobacter junii is a rare human pathogen associated with bacteraemia in neonates and paediatric oncology patients. We report a unique case of bacteremia caused by Acinetobacter junii, in a patient with no risk factors identified.